THE ALTERNATIVE DILUTE SOLUTION OF NaCl 0.9% AT THE GIEMSA STAINING ON THE INVESTIGATION THE MORPHOLOGY OF SPERMATOZOA - Maruni Wiwin Diarti; Erlin Yustin Tatontos; Aden Turmuji (poltekkes kemenkes mataram, 2016)
Abstract : The quality of staining, the morphology of spermatozoon applays The Giemsa dye, is strongly influenced by the type of Giemsa thinner. The terms of diluent that can be used is having a buffer property. The solution of NaCl 0.9 %, besides having buffer properties also has a cheaper price. The research is a descriptive study that aims to determine NaCl 0.9% as the alternative of diluting solution at Giemsa staining on morphological examination of spermatozoon. This study was conducted to compare the quality of spermatozoon morphology staining by using Giemsa which was diluted with 0.9% NaCl solution and the solution of Phosphate Buffer. The result of the study indicated The Giemsa staining with NaCl 0.9% solution, is obtained the outstanding spermatozoon morphology staining absorption was 71.625% and the poor spermatozoon morphology staining absorption was 28.375%. The results of study which was applied the Phosphate Buffer solution, was obtained the outstanding spermatozoon morphology staining absorption was 81.563% and the poor spermatozoon morphology staining absorption was 18.438%. The NaCL 0.9% can be used as an alternative dilute solution at Giemsa staining on morphological examination of spermatozoon.